2016
DOI: 10.1007/s12149-016-1079-6
|View full text |Cite
|
Sign up to set email alerts
|

Report of a nationwide survey on actual administered radioactivities of radiopharmaceuticals for diagnostic reference levels in Japan

Abstract: ObjectiveThe optimization of medical exposure is one of the major issues regarding radiation protection in the world, and The International Committee of Radiological Protection and the International Atomic Energy Agency recommend establishing diagnostic reference levels (DRLs) as tools for dose optimization. Therefore, the development of DRLs based on the latest survey has been required for nuclear medicine-related societies and organizations. This prompted us to conduct a nationwide survey on the actual admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Compromises on image quality may be offset by increasing scan duration. Internationally, the reported AU QLD/WA DRL study and the proposed NZ NDRL study were within the range of previously published values (200–500 MBq) (Table ) . However, the reported AU QLD/WA DRL and the proposed NZ NDRL are higher than the France published NDRL based on TOF technology, which was 260 MBq .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Compromises on image quality may be offset by increasing scan duration. Internationally, the reported AU QLD/WA DRL study and the proposed NZ NDRL study were within the range of previously published values (200–500 MBq) (Table ) . However, the reported AU QLD/WA DRL and the proposed NZ NDRL are higher than the France published NDRL based on TOF technology, which was 260 MBq .…”
Section: Discussionsupporting
confidence: 82%
“…Published articles reported 18 F‐FDG PET/CT DRL values for the administered activity or CT used for AC and anatomical localization purposes, with few authors reporting both radiation doses . PET/CT DRLs from both radiation sources should be reported to provide suitable guidelines for professionals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of DRLs for PET/CT and SPECT/CT imaging is an essential step in recognising variations between radiation doses delivered to the patient using a diverse range of equipment and changing protocols (14) . The existing PET/CT and SPECT/CT, PET, SPECT, and CT component methods are prone to some limitations due to diverse methods implemented for population selection, different reporting methods, the impact of new imaging technology, and reporting effective dose (E) from both the A and CT (15,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . The purpose of this systematic review is to determine the variations in reported NDRL methodology and values for adult PET/CT and SPECT/CT procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe and colleagues reported on a national survey of the actual administered radioactivity to adults for a variety of single-photon radiotracers as well as for FDG (59). The nationwide survey was conducted for nearly 2 months from November 25, 2014 to January 16, 2015 and was sent to 1249 nuclear medicine facilities in Japan.…”
Section: National Surveymentioning
confidence: 99%